Unofficial Choronyms of Vilnius: a Reflection of Youth Language - Sidaravičienė, Veslava (Respectus Philologicus, 2023)
The article discusses the formation of unofficial choronyms in Vilnius based on their linguistic characteristics. The study reveals that unofficial choronyms are formed based on three main processes: 1) by deriving from official choronym or their parts, e.g. Fabai (derived from Fabijoniškės), Baltuša (from Baltupiai); 2) by using a named place as the basis, e.g. Bomžynas (Naujininkai): bomžynas (LKŽŽ 90) “where poor people live”), Lušnynas (Kirtimai): lūšnynas (“refers to many dilapidated houses in the district”); and 3) by combining an official choronym with a named place, like Fabibiškės (derived from Fabijoniškės) ← Fabi[jon]iškės + bibi[s], and Seilėtekis (from Saulėtekis) ← S[au]lėtekis + seilė. The trends in the spoken language of young people demonstrate a tendency to use short forms of the official name-based choronyms, reflecting principles of language economy. The largest subgroup in terms of numbers is motivated unofficial choronyms, accounting for 56% of the examples. Another aspect important in the development of new names is the need to give names and imbue them with emotional and expressive qualities. Names based on associations make a smaller proportion (36%), while the third group is the least common (8%).
Keywords: unofficial choronyms; unofficial urbanonyms; choronyms; the ways of forming choronyms; youth language